2006
DOI: 10.1007/7140.2006.00010
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigus in North India

Abstract: North Indian patients of pemphigus have a relatively younger age at onset. The majority of patients were from the states of Punjab and Haryana. The response to DCP therapy was good, and with DCP, the additional dose of oral steroids that was required to control the activity of the disease was less than 30 mg/d, which is much less than the dosage used in the standard conventional regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 33 publications
(63 reference statements)
2
25
1
2
Order By: Relevance
“…In another study, concurrent steroid therapy along with antibiotics for secondary infection, if any, was found to be more effective in inducing remission earlier and shortening duration of phase I. [2] Kanwar et al [4,5] in their series reported that the response to pulse therapy was faster in the milder form of disease; the severe form of disease requiring more number of pulses as well as higher doses of intervening oral corticosteroids. These results are similar to those of our study.…”
Section: Discussionmentioning
confidence: 95%
“…In another study, concurrent steroid therapy along with antibiotics for secondary infection, if any, was found to be more effective in inducing remission earlier and shortening duration of phase I. [2] Kanwar et al [4,5] in their series reported that the response to pulse therapy was faster in the milder form of disease; the severe form of disease requiring more number of pulses as well as higher doses of intervening oral corticosteroids. These results are similar to those of our study.…”
Section: Discussionmentioning
confidence: 95%
“…6 Few studies have reported a significant male preponderance (3:1, 3:2) whereas certain studies have shown significant female preponderance (0.8:1, 1:1.2). [12][13][14][15] In a study by Babu et al, 71.4% of their cases were females and majority of their patients fell in the age group of 30-40 years. Their results suggested that pemphigus was observed in 7/3,500 dermatological patients during 8 months of their study.…”
Section: Discussionmentioning
confidence: 99%
“…[28,29] Pemphigus is rare in children and in our previous study, children aged less than 15 years accounted for 3.7% of all cases. [1] A recent review of the English literature found 33 cases of childhood pemphigus (aged <12 years) and 47 cases of juvenile pemphigus (aged 12-18 years). [30,31] Treatment modalities reported included systemic corticosteroids, azathioprine, dapsone, and IVIG.…”
mentioning
confidence: 98%
“…A significant proportion of pemphigus patients have been less than 40 years of age. [1] It is a common disorder in India; however there is lack of population based studies and most studies are hospital based. The incidence of pemphigus among the dermatology outpatient attendees has varied widely, 0.09-1.8%.…”
mentioning
confidence: 99%
See 1 more Smart Citation